Possibilities of forming a responsible attitude to the environment in students of psychological and pedagogical sciences - Mamirova Zuhrakhan (Periodica Journal, 2022)
In this article, in accordance with the general pedagogic theories and principles of ecology, the content of ecological education reveals the scientific, valuable, normative and functional aspects of society's interaction with nature, and the global importance of ecological problems and the ideas of optimizing the use of nature
Keywords: Anthropogenesis; matter; ectetic; ecological